Consumo de Canábis: craving e a relação com ansiedade, stresse e depressão - José Vasconcelos-Raposo; Sérgio Couto; Nilton Formiga; Carla M. Teixeira (Actualidades en Psicología, 2018)
Cannabis is the most used illicit substance in Portugal and is the one, which presents, on average, an earlier onset of consumption. Craving is considered one of the fundamental factors linked to the cannabis use, associating anxiety, stress and depression. The sample consisted of 143 individuals from the northern area of the country and the data was gathered through two online questionnaires (DASS-21 and the MCQ-SF). The obtained results allow us to conclude that emotionality, purposefulness and compulsivity are positively associated with the level of craving and, combined, as well to stress and depression. The number of years of consumption presents a significant effect in anxiety, with a medium effect size.